PENERAPAN TEKNOLOGI SMART FARMING BERBASIS INTERNET OF THINGS BAGI MASYARAKAT PETANI JERUK SIAM - Zulkarnain, Andry Fajar; Wijaya, Eka Setya; Mustamin, Nurul Fathanah (Batara Wisnu : Indonesian Journal of Community Services, 2022)
South Kalimantan Province is one of the areas of agricultural land suitable for Siamese citrus. But several problems can affect the decline in Siam Banjar citrus production and must be prevented immediately so that production rates remain stable and can continue to increase, one of which is farmers in Indonesia who still depend on the rainy season to grow crops and will experience drought problems during the dry season. Come. That’s why, along with the development of current technology, one of which is in the agricultural sector, with the help of Internet of Things (IoT) technology, a tool is made, namely automatic watering using the Fuzzy Logic Control method. There are several advantages when using the help of the Internet of Things (IoT), such as water that will be real-time, comprehensive water intake, and following the state of the plant at that time. It is hoped that with the help of this device, Siamese orange farmers can get better harvests in the future